Measurement of long-range pseudorapidity correlations and azimuthal harmonics in root s(NN)=5.02 TeV proton-lead collisions with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; et al. (American Physical Society, 2014)
Measurements of two-particle correlation functions and the first five azimuthal harmonics, v1 to v5, are presented, using 28 nb-1 of p+Pb collisions at a nucleon-nucleon center-of-mass energy of sNN=5.02 TeV measured with the ATLAS detector at the LHC. Significant long-range "ridgelike" correlations are observed for pairs with small relative azimuthal angle (|Δφ|<π/3) and back-to-back pairs (|Δφ|>2π/3) over the transverse momentum range 0.4<pt<12 0.1="" 5="" a="" about="" activity="" activity.="" also="" and="" are="" around="" as="" azimuthal="" be="" by="" change="" correlations="" decomposed="" decrease="" defined="" different="" either="" energy="" event="" extracted="" for="" found="" fourier="" function="" gev="" harmonics="" in="" increase="" intervals="" is="" long-range="" measured="" n="2" n.="" number="" observed="" obtain="" of="" on="" or="" pb-fragmentation="" positive="" pt="" pt≈1.5-2.0="" range.="" reconstructed="" side.="" sign="" structure="" such="" the="" then="" to="" total="" tracks="" transverse="" v1="" v2="" v3="" values="" vn="" with="">4 GeV. The v2(pT), v3(pT), and v4(pT) are compared to the vn coefficients in Pb+Pb collisions at sNN=2.76 TeV with similar event multiplicities. Reasonable agreement is observed after accounting for the difference in the average pT of particles produced in the two collision systems.</pt<12>